A atividade eólica e o desenvolvimento regional: perspectivas na formação do pólo eólico no Rio Grande do Norte - Amaral Neto, Raimundo Pereira do (2012)
The object of this study involves the eolian energy and the scenario the training of wind pole in Rio Grande do Norte. The aim is to investigate how far the implementation of the potiguar eolian pole may represent a regional development policy with real change in the structure of the traditional local productive base. About the interaction between the public and private to development of the local eolian activity, the hypothesis is that there is no coordination between the sectors responsible for eolian activity in the state. The theoretical approach follows the developmental current and theory of growth poles, and methodology adopted is a search of exploratory and documentary, with analysis of relevant documents on the subject. As a result of the study it was found that owing to the fragility of the productive structure potiguar and imbalances produced by the concentration of capital in the Northeast, the eolian activity in the state, needs a greater state-owned intervention to ensure a basis of development based on the study and strengthening local productive chain